ABOUT DALAT’S CULTURAL NORMS - Nguyễn Văn Nghiệp; Trịnh Như Phong (Tạp chí Khoa học Đại học Đà Lạt)
In order to preserve and promote the "peaceful, elegant, and hospitable" style of Dalat people, the article presents the principles when grinding Dalat's cultural norms, some contents of the ministry, and difficulties in developing and applying this set of rules.